Adherent Bacteria and Parasiticidal Secretion Products of Human Cervicovaginal Microbiota-Associated Lactobacillus gasseri Confer Non-Identical Cell Protection against Trichomonas vaginalis-Induced Cell Detachment - Bénédicte Pradines; Séverine Domenichini; Vanessa Lievin-Le Moal (MDPI AG, 2022)
Trichomonas vaginalis, a protozoan parasite specific to the human genital tract, is one of the most common sexually transmitted pathogens. Its pathogenicity is strongly associated with its expression of a broad array of proteases triggering cytotoxic effects in host epithelial cells. Vaginal microbiota-associated Lactobacillus, including those of L. gasseri in particular, can counteract T. vaginalis pathogenesis, but the mechanisms involved have yet to be clarified. T. vaginalis strain G3 (Tv G3) cytotoxicity was assessed by examining cell morphology, cell detachment, and fluorescent labeling of the F-actin cytoskeleton and immunolabeling of vinculin-position focal adhesions (FAs) by confocal laser scanning electron microscopy on confluent cervicovaginal epithelial HeLa cell monolayers. The inhibitory effects of bacterial cells and secreted products of L. gasseri ATCC 9857 and KS 120.1 on the Tv G3 viability and parasite deleterious effects on HeLa cells were investigated. Pre-adhering L. gasseri cells delayed but did not inhibit Tv G3-induced cell detachment, F-actin cytoskeleton disorganization and the disappearance of vinculin-positive focal FAs. L. gasseri KS 120.1 secretion products had a rapid parasiticide activity by killing time- and concentration-dependent Tv G3 parasites after direct contact. By killing Tv G3 parasites already associated with the epithelial cells, secretion products have abolished parasite-induced cell detachment. Our findings suggest that vagina microbiota-associated L. gasseri creates a physical barrier and exerts pharmacological-type mechanisms to counteract the deleterious cytotoxic effects of T. vaginalis.